Essays in macroeconomics and finance - Bianchi, Benedetta (Trinity College (Dublin, Ireland). Department of Economics, 2017)
This dissertation consists of three essays, which deal with issues relating to the financial sector. Although the three chapters are independent, a common underlying theme is financial crises. The first essay studies the varying perception of the risk attributed to European sovereign bonds. There was a shift in risk perception after 2009, most evident in the relation between sovereign risk and net foreign assists. Before the breakout of the Euro debt crisis, the external imbalances accumulated by the poorer countries in the Euro periphery were interpreted to be the result of a natural convergence process which induced net capital inflows towards poorer, relatively more productive countries. Later, the same imbalances were seen as one of the main factors of financial distress in crisis countries. We investigate the role of market uncertainty in the relation between net foreign assets and sovereign risk in the years following the introduction of the euro up to the end of the sovereign debt crisis (2000-2013). Furthermore, we ask which component of the international balance sheet, in terms of debt and equity instruments, is most relevant in explaining the external-sovereign nexus. We find that a negative net foreign asset position can have a negative or positive relation with sovereign yield spreads. Portfolio equity and EDI are related to sovereign risk in a stable manner, while net negative external debt as large as GDP can be associated with government yield spread spikes as high as 3%.
Keywords: Economics, Ph.D.; PhD Trinity College Dublin, 2017